1998
DOI: 10.1148/radiology.206.2.9457193
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of thrombosed hemodialysis access grafts: Arrow-Trerotola percutaneous thrombolytic device versus pulse-spray thrombolysis. Arrow-Trerotola Percutaneous Thrombolytic Device Clinical Trial.

Abstract: The PTD is safe and effective for treating thrombosed hemodialysis access grafts. The technical and long-term success rates are similar to those of PSPMT; procedure times are shorter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
4

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(75 citation statements)
references
References 0 publications
4
67
0
4
Order By: Relevance
“…The patency rates 6 and 12 months after thrombolysis were 62 -80 % and 57 -69 %, respectively. Trerotola and colleagues demonstrated a 95 % primary success rate with a patency rate after 3 months of 39 % as a result of the use of PTD [84]. Compared to different mechanical thrombolysis instruments, Smits et al concluded that the treatment of the underlying stenosis was the only relevant factor for the treatment success of a thrombosed dialysis graft [85].…”
Section: Insufficient Dialysis Graftmentioning
confidence: 99%
“…The patency rates 6 and 12 months after thrombolysis were 62 -80 % and 57 -69 %, respectively. Trerotola and colleagues demonstrated a 95 % primary success rate with a patency rate after 3 months of 39 % as a result of the use of PTD [84]. Compared to different mechanical thrombolysis instruments, Smits et al concluded that the treatment of the underlying stenosis was the only relevant factor for the treatment success of a thrombosed dialysis graft [85].…”
Section: Insufficient Dialysis Graftmentioning
confidence: 99%
“…Subsequently, other publications demonstrated equivalent efficacy of other devices when compared to thrombolytic therapy [5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Accepted treatments for acutely occluded access grafts include surgery and thrombolytic therapy/angioplasty [3]. Several mechanical thrombectomy devices have been developed recently in efforts to lessen the invasiveness and cost of surgery and decrease complications related to thrombolytic therapy [4][5][6][7]. One of the first mechanical thrombectomy devices to be developed, and the first to be approved for the US market, was the Amplatz thrombectomy device (ATD); however, the final results in the trial comparing the ATD with surgical thromboembolectomy (ST) to declot occluded DAG had yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of methods, including pulsespray pharmacomechanical thrombolysis, balloon-assisted thrombectomy, and several mechanical thrombectomy devices have been developed for the treatment of thrombosed hemodialysis grafts (3)(4)(5)(6)(7)(8). The dual access approach has been the most adopted method for performing percutaneous thrombectomy in loop-configured grafts.…”
Section: Discussionmentioning
confidence: 99%